2001
DOI: 10.1046/j.1365-2249.2001.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell recovery is slower in patients experiencing viral load rebounds during HAART

Abstract: SUMMARYTo determine whether viral load rebounds during HAART impact on CD4 1 T cell recovery and immune reconstitution, we studied a prospective cohort of 355 antiretroviral naive patients enrolled to be randomized in a trial of three strategies of induction/maintenance HAART. The extent of immune reconstitution in blood through 72 weeks of antiretroviral treatment was evaluated. Lymphocyte subset markers (CD4, CD8, CD45RA, CD62L, CD16, CD19), activation markers (HLA-DR, CD38, CD25) were performed by cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…However, this does not concur with other reports [Lu and Andrieu, 2000;Baldanti et al, 2001;Scott-Algara et al, 2001], that documented similar results in the two groups. This could be due to a different definition of partial responders and/or …”
Section: Optimal Cd4contrasting
confidence: 98%
See 2 more Smart Citations
“…However, this does not concur with other reports [Lu and Andrieu, 2000;Baldanti et al, 2001;Scott-Algara et al, 2001], that documented similar results in the two groups. This could be due to a different definition of partial responders and/or …”
Section: Optimal Cd4contrasting
confidence: 98%
“…þ T cell count long-term response is related to the degree and durability of viral load suppression, as other researchers have also reported in a 2-year followup studies [Deeks et al, 1999[Deeks et al, , 2000Mezzaroma et al, 1999;Notermans et al, 1999;Renaud et al, 1999;Connick et al, 2000;Kaufmann et al, 2000;Wood et al, 2000;Scott-Algara et al, 2001] and in up to 32 months follow-up [Teixeira et al, 2001]; however other researchers have found a similar increase in the two groups [Lu and Andrieu, 2000;Baldanti et al, 2001].…”
Section: Optimal Cd4mentioning
confidence: 69%
See 1 more Smart Citation
“…Although the occurrence of measles reinfection has not been reported in HIV-1-infected adults, an increased rate of measles infections and deaths occur in infants born to HIV-1-infected mothers living in geographic areas with poor access to measles vaccination. 16,17,19,23 Moreover, although not exhaustively addressed here, it is conceivable that memory B cells specific to other relevant antigens are reduced in HIV-1 infection. This would, for instance, include pathogens such as S pneumoniae, which has a well-characterized clinical relevance for HIV-1 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have suggested that a compromised memory B-cell response and/or low specific antibody titers may increase the risk of infections for the HIV-1 carrier 10,[13][14][15] and for children born to HIV-1-infected mothers. [16][17][18][19] To further dissect the relationship between loss of memory B cells, reduction of specific antibody levels, and disease progression, we studied subjects at different stage of disease (ie, PHI, CHI, and long-term nonprogressor [LTNP]) and also evaluated the effects of ART. In order to cover the spectrum of currently held views on maintenance of B-cell memory, we measured Ab titers against a T-cell-dependent antigen (measles) and a T-cell-independent antigen (pneumococcal polysaccharide capsule antigen [PPS]).…”
Section: Introductionmentioning
confidence: 99%